The impact of fluctuations in the dinar exchange rate on the balance of payments in Algeria during the period 2000-2014 - Srarma, Abdlwahid; Baaloul, Noufel (Milev Journal of Research and Studies, 2017)
This paper aims to analyze the effect of exchange rate fluctuations on the balance of payments of Algeria during the period 2000-2014. the applied results indicated through the econometric model to prove that the exchange rate does not affect the Algerian balance of payments, And the policy of devaluation of the currency have no impact on improving the status of the overall balance during the study period. The study concluded that there was an inverse relationship between the exchange rate and the balance of payments, and Granger's causality test showed that there was no causation trend from the exchange rate to the balance of payments .